The Rapid Cytological Process of Grain Determines Early Maturity in Weedy Rice - Zhao, Can; Xu, Wenrong; Li, Hewei; Dai, Weimin; Zhang, Zheng; Qiang, Sheng; Song, Xiaoling (Frontiers in Plant Science, 2021)
Shorter grain-filling period and rapid endosperm development endow weedy rice (WR) with early maturity compared to cultivated rice (CR). However, the role of the cytological features and antioxidative enzyme system during grain development are largely unexplored. We selected four biotypes of WR and their associated cultivated rice types (ACR) from different latitudes to conduct a common garden experiment. The difference in the cytological features of endosperm between WR and ACR was compared by chemical staining, and the cell viability and nuclear morphometry of endosperm cells were observed by optical microscopy. Furthermore, antioxidative enzyme activity was measured during grain filling. Anatomic observation of endosperm shows that the development process of endosperm cell in WR was more rapid and earlier than that in ACR. The percentage of degraded nuclei of WR was 3%-83% more than that of ACR. Endosperm cells in WR lost viability 2-6 days earlier than those in ACR. The antioxidant enzyme activity of WR was lower than that of ACR during grain filling. The ability of WR to scavenge reactive oxygen species was weaker than that of ACR, which may contribute to the rapid cytological process in the endosperm cells of WR. The rapid cytological process and weaker ability to scavenge reactive oxygen species in endosperm cells may contribute to early maturity in WR.